The Wiser Barn (Symphony in the Flint Hills, 2012)
An Image of Wiser Barn and a Lithograph of Wiser Barn and Ranch. Ellen Coffman has shared her knowledge with Michael Stubbs, Historical Research Editor of the Field Journal, about this historical building.
Keywords: Wiser Barn; history; Kansas; prairie; grassland; ranch; Wabaunsee County; Ellen Coffman; Chicago World& #x27; s Fair; Dion Geraldine; J.P. Wiser; Hick& #x27; s Orchestra; farm; Grover Cleveland